Respuesta :
Answer:
d
Step-by-step explanation:
becasuse when you multiply all that stuff since x is the is y fancy way o f saying
From the calculations, we can see that the true statement is f(-3) = g(-2): Option D is correct.
Given the following functions
f(x) = (2x + 1)²– 3 and g(x) = 2(2x² + 3),
According to the last option.
f(-3) = (2(-3) + 1)²– 3
f(-3) = (-6+1)² - 3
f(-3) = (-5)² - 3
f(-3) = 25 - 3
f(-3) = 22
For g(-2)
g(-2) = 2(2x² + 3),
g(-2) = 2(2(-2)² +3)
g(-2) = 2(8+3)
g(-2) = 2(11)
g(-2) = 22
Hence from the calculations, we can see that the true statement is f(-3) = g(-2)
Learn more here: https://brainly.com/question/23207600